2010
DOI: 10.1002/nbm.1488
|View full text |Cite
|
Sign up to set email alerts
|

NMR metabolic profile of human follicular fluid

Abstract: The environment of the oocyte during its in vivo maturation consists of follicular fluid (FF) and is surrounded by granulosa cells. The FF is derived from the sanguineous plasma and secretions, synthesised in the follicle wall, that contain a large variety of growth factors, cytokines, amino acids, and other metabolites. These metabolites are presumably involved in the physiology of the oocyte. The identification, quantification and study of FF metabolites can provide additional information about the oocyte st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 41 publications
(49 reference statements)
5
58
1
Order By: Relevance
“…To date, there are relatively few reports of the use of NMR spectroscopy to analyse FF samples (reviewed by Baskind et al (2011)), and to our knowledge, there is only one other report of this method being used to determine the composition of porcine FF (Gosden et al 1990). Recent reports of the use of this technology to identify potential biomarkers of oocyte quality (Pinero-Sagredo et al 2010, McRae et al 2012, Wallace et al 2012 and polycystic ovarian syndrome (Atiomo & Daykin 2012) in FF collected from women undergoing fertility treatments highlight its potential. Our findings demonstrate the effectiveness of 1 H-NMR spectroscopy in detecting metabolite differences in intact, untreated FF collected from individual animals and extend the knowledge gained from 1 H-NMR studies in other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are relatively few reports of the use of NMR spectroscopy to analyse FF samples (reviewed by Baskind et al (2011)), and to our knowledge, there is only one other report of this method being used to determine the composition of porcine FF (Gosden et al 1990). Recent reports of the use of this technology to identify potential biomarkers of oocyte quality (Pinero-Sagredo et al 2010, McRae et al 2012, Wallace et al 2012 and polycystic ovarian syndrome (Atiomo & Daykin 2012) in FF collected from women undergoing fertility treatments highlight its potential. Our findings demonstrate the effectiveness of 1 H-NMR spectroscopy in detecting metabolite differences in intact, untreated FF collected from individual animals and extend the knowledge gained from 1 H-NMR studies in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Characterisation of FF can provide useful information about the growth and differentiation of the follicle (Edwards 1974). Various studies performed in mammals clearly demonstrate that FF contains components essential to oocyte maturation and fertilisation and molecules related to follicular cell proliferation and differentiation (Gérard et al 2002, Pinero-Sagredo et al 2010. Owing to the close physical relationship between the COC and the FF, analysis of this fluid is of extreme interest for elucidating the determinants of oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, complementary observations that may reflect this link between follicular-cell-secreted amino acids and the gamete have shown that the concentrations of some amino acids in follicular fluid change, depending on follicle dominance status and estrous cyclicity (Orsi et al 2005). Others have reported that some amino acids are involved in the physiology of the oocyte and are required for oocyte maturation, fertilization, and preimplantation development and can be used, in many species, as a marker of embryo developmental competence or fertility outcome (D'Aniello et al 2007, Hong & Lee 2007, Sinclair et al 2008, Pinero-Sagredo et al 2010. Taken together, these results suggest that protein degradation occurring before the LH surge could be utilized for amino acid bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have examined FF composition using NMR technology and found associations between lipoproteins and oocyte/embryo outcomes [61][62][63][64]. However, these studies were limited by the absence of a Bone-follicle, oneembryo^design and most were not conducted in humans.…”
Section: Geometric Mean Concentration (µMol/l) Hdl-c Subfractions (Nm)mentioning
confidence: 99%